The pilgrim church being some account of the continuance through suceeding centuries of churches practising the principles taught and exemplified in the New Testament - Broadbent, Edmund Hamer, 1861-1945 (London, UK Pickering and Inglis, 1931)
Includes bibliographical references and index.
Brethren writer. Copies 1 and 2 in archives.
Keywords: Church history; Brethren movement -- historical basis